Revisiting beta thalassemia intermedia: past, present, and future prospects. Issue 10 (26th November 2017) - Ben Salah, Naouel; Bou-Fakhredin, Rayan; Mellouli, Fethi; Taher, Ali T.
ABSTRACT: Background: The spectrum of thalassemias is wide ranging from thalassemia minor, which consists of mild hypochromic microcytic anemia without obvious clinical manifestations, to thalassemia major (TM), which is characterized by severe anemia since the first years of life and is transfusion dependent. Thalassemia intermedia (TI) describes those patients with mild or moderate anemia. Objective: To describe the genetic features and major clinical complications of TI, and the therapeutic approaches available in the management of this disease. Methods: Publications from potentially relevant journals were searched on Medline. Results and discussion: Over the past decade, the understanding of TI has increased with regard to pathophysiology and molecular studies. It is now clear that clinical presentation and specific complications make TI different from TM. It is associated with greater morbidity, a wider spectrum of organ dysfunction and more complications than previously thought. Conclusion: TI is not a mild disease. The interplay of three hallmark pathophysiologic factors (ineffective erythropoiesis, chronic anemia, and iron overload) leads to the clinical presentations seen in TI. New treatment modalities are currently being investigated to broaden the options available for TI management.